PENDIDIKAN KESEHATAN TENTANG DETEKSI DINI KANKER SERVIKS PADA PEREMPUAN USIA SUBUR - Yessi Andriani; Vera Sesrianty; Mera Delima (Jurnal Pengabdian Mitra Masyarakat (JPMM), 2020)
Women's health is a parameter of the country's ability to provide health services to the community. Health has various kinds of scope that must be fulfilled, one of the scope of health is reproductive health. Reproductive health is physical health, mental and social intact and not only the absence of disease or weakness in all matters relating to the reproductive system and its functions and processes. Cervical cancer is a type of cancer that occurs in the cervix or the cervix, which is the lower area of the uterus that connects the uterus and vagina. Cervical cancer will usually show serious symptoms, after the next 10-20 years in women who are married or sexually active. Cervical cancer is a disease with the highest prevalence in Indonesia in 2018, which is 0.8% of Indonesia's population or an estimated 98,692 patients (Riskesdas, 2018). Many people with cervical cancer only realize after examining for treatment and diagnosed that the stage of the cancer is already acute because in the precancerous and early stages, this type of cancer often shows no symptoms at all, so it can be detected early to find out if there is a reciocancer. IVA (Visual Inspection with Acetic Acid) is one way for early detection of cervical cancer by looking directly at the cervix after daubing the cervix with 3-5% acetic acid solution. If after stroking acetic acid 3-5% there is a change in color, which appears white spots, then an indication of cancer lesions. The general objective of IVA examination is to reduce morbidity and mortality due to cancer so that health education needs to be provided which aims to increase people's motivation to conduct routine health checks.